Oral health status, awareness, attitude, practices, and level of nicotine dependence among Tamil Nadu Electricity Board workers in North Chennai, Tamil Nadu - T C Bharathi; K Kavitha; R Ganesh (Wolters Kluwer Medknow Publications, 2016)
Aim: To assess the oral health status, awareness, attitude, practices, and level of nicotine dependence among electricity board workers in North Chennai, Tamil Nadu. Subjects and Methods: A cross-sectional study was conducted among the electricity board workers in North Chennai. About 285 electricity board workers answered the questionnaire regarding the oral health awareness, attitude, practices, and also Fagerstrom nicotine dependence questionnaire was used to record the tobacco usage. After answering the questionnaire, the subjects were examined using the mouth mirrors and probe under natural light for recording the oral health status using oral hygiene index-simplified index and decayed, missing, and filled teeth (DMFT) index. Statistical Analysis Used: SPSS version 21. Results: The mean DMFT of electricity board workers was 4.168 ± 2.766. About 91.6% of electricity board workers were with fair oral hygiene status. Prevalence of smoking among the study subjects was 26.7% and smokeless tobacco was 9.1%. Conclusions: The finding of the study provides the insight into the oral health status and awareness among electricity board workers in North Chennai. The oral health status of the electricity board workers is in a fair state. Steps should be taken so as to provide basic dental care facilities for the workers.